Intraoperative Alcoholization of the Pituitary Gland Does Not Reduce the Recurrence Rate of Growth Hormone Secreting Pituitary Adenomas - Gill, Amarbir S.; Sumsion, Jorgen; Alt, Jeremiah A.; Karsy, Michael; Couldwell, William T.; Menacho, Sarah T. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Objective Although the role of intraoperative alcoholization of the pituitary gland has been examined for the management of malignant tumor metastases and Rathke's cleft cysts, no such studies have been conducted relating to growth hormone (GH) secreting pituitary tumors, despite the high rate of recurrence in this cohort of patients. Here, we sought to understand the impact of adjunctive intraoperative alcoholization of the pituitary gland on recurrence rates and perioperative complications associated with resection of GH-secreting tumors.Methods This is a single-institution retrospective cohort study analyzing recurrence rates and complications among patients with GH-secreting tumors who received intraoperative alcoholization of the pituitary gland postresection versus those that did not. Welch's t-tests and analysis of variance (ANOVA) analyses were employed to compare continuous variables between groups, whereas chi-squared tests for independence or Fisher's exact tests were used for comparing categorical variables.Results A total of 42 patients (n = 22 no alcohol and n = 20 alcohol) were included in the final analysis. The overall recurrence rates did not significantly differ between the alcohol and no alcohol groups (35 and 22.7%, respectively; p = 0.59). The average time to recurrence in the alcohol and no alcohol groups was 22.9 and 39 months, respectively (p = 0.63), with a mean follow-up of 41.2 and 53.5 months (p = 0.34). Complications, including diabetes insipidus, were not significantly different between the alcohol and no alcohol groups (30.0 vs. 27.2%, p = 0.99).Conclusion Intraoperative alcoholization of the pituitary gland after resection of GH-secreting pituitary adenomas does not reduce recurrence rates or increase perioperative complications.
Keywords: pituitary gland; intraoperative alcoholization; growth hormone–secreting tumors; perioperative complications; pituitary tumor